Marvel comics' Civil War and the age of terror : critical essays on the comic saga - Scott, Kevin M.; Scott, Kevin M.; Weiner, Robert G.; DiPaolo, Marc (McFarland & Company, Inc., Publishers, 2015)
"With the publication of 'Civil War' (2006-2007), a seven-issue crossover storyline spanning the Marvel universe, Marvel Comics focused on contemporary anxieties. This collection of essays explores the 'Civil War' series and its many tie-in titles from the perspectives of history, political science, sociology, psychology, literary criticism, law, philosophy and education"--